2022
DOI: 10.3390/ijerph19010583
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Kangaroo Mother Care in the NICU on the Physiological Stress Parameters of Premature Infants: A Meta-Analysis of RCTs

Abstract: Objective: The aim of this study was to analyze the randomised controlled trials that explored the effect of kangaroo mother care on physiological stress parameters of premature infants. Methods: Two independent researchers performed a systematic review of indexed studies in PubMed, Embase, CINAHL, Cochrane and Scopus. We included data from randomized controlled trials measuring the effects of kangaroo care compared to standard incubator care on physiological stress outcomes, defined as oxygen saturation, body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 33 publications
1
8
0
3
Order By: Relevance
“…Improved infantmother interaction could have appositive effect on reducing pain and stress in premature infants. This finding was in line with Johnston et al, 2017, Johnston et al, 2018, Akcan et al, 2019and Souza-Vogler & Lima, 2021and Cristóbal Cañadas et al, 2022 They notified that supportive care helped to reduce levels of neonatal pain and stress.…”
Section: Discussionsupporting
confidence: 56%
“…Improved infantmother interaction could have appositive effect on reducing pain and stress in premature infants. This finding was in line with Johnston et al, 2017, Johnston et al, 2018, Akcan et al, 2019and Souza-Vogler & Lima, 2021and Cristóbal Cañadas et al, 2022 They notified that supportive care helped to reduce levels of neonatal pain and stress.…”
Section: Discussionsupporting
confidence: 56%
“…SSC, also known as KC, refers to the way the mother holds a diaper-clad infant upright on her breast at approximately 60°, providing maximum skin-to-skin contact between the baby and mother 45. Studies have shown that KC can not only reduce pain and stabilise the physiological and behavioural responses of the neonates, but it also strengthens the mother–infant bonding 56 57. Furthermore, no significant difference in pain scores was found between the mother and other providers (father and another woman) 45.…”
Section: Discussionmentioning
confidence: 99%
“… 16 A recent review described the heterogeneity of studies on SSC and cardiorespiratory outcomes. 17 A dose-response relationship has been hypothesized, but one study confirms a positive effect on the physiology of very low birth weight infants even with hour-long sessions of SSC. 18 The importance of early tactile stimulation for positive neurodevelopmental experiences is well-described, 19 , 20 as well as mother-infant separation as a source of toxic stress.…”
Section: Introductionmentioning
confidence: 99%